Evaluation of antileishmanial activity of harzialactone a isolated from the marine-derived fungus Paecilomyces sp - Braun, Glaucia H. [UNESP]; Ramos, Henrique P.; Candido, Ana C. B. B.; Pedroso, Rita C. N.; Siqueira, Kátia A.; Soares, Marcos A.; Dias, Gustavo M.; Magalhães, Lizandra G.; Ambrósio, Sérgio R.; Januário, Ana H.; Pietro, Rosemeire C. L. R. [UNESP] (Taylor & Francis, 2019)
Fractionation of extracts from the culture broth of the marine-derived fungus, Paecilomyces sp. 7A22, resulted in the isolation of the harzialactone A (HA), a known compound previously isolated from fungi of marine environments. The chemical structure of HA was determined by spectroscopic analyses. Upon evaluation of HA on antileishmanial assays against Leishmania amazonensis, HA exhibited significant activity against promastigotes forms with IC50 of 5.25 µg mL−1 and moderate activity against intracellular amastigotes with IC50 of 18.18 µg mL−1. This is the first report on the antileishmanial activity of HA, and the effects of HA presented in this work suggest that this class of compounds are suitable for future biological in vitro and in vivo studies for the search of natural products with activity against Leishmania spp. Furthermore, the present results corroborate marine-derived fungi as a promising source of natural products with antiparasitic activity.
Keywords: Aplidiopsissp; harzialactone A; leishmanicidal activity; Paecilomyces sp